Trajectory and Functional Analysis of PD‐1high CD4+CD8+ T Cells in Hepatocellular Carcinoma by Single‐Cell Cytometry and Transcriptome Sequencing. Issue 13 (18th May 2020) - Zheng, Bo; Wang, Dongfang; Qiu, Xinyao; Luo, Guijuan; Wu, Tong; Yang, Shuai; Li, Zhixuan; Zhu, Yanjing; Wang, Shan; Wu, Rui; Sui, Chengjun; Gu, Ziqi; et al.
Abstract: The spatial heterogeneity of immune microenvironment in hepatocellular carcinoma (HCC) remains elusive. Here, a single‐cell study involving 17 432 600 immune cells of 39 matched HCC (T), nontumor (N), and leading‐edge (L) specimens by mass cytometry is conducted. The tumor‐associated CD4/CD8 double‐positive T (DPT) cells are found enriched in L regions with synergetic expression of PD‐1/HLA‐DR/ICOS/CD45RO and exhibit a higher level of IFN‐ γ, TNF‐ α, and PD‐1 upon stimulation. The enrichment of DPT and PD‐1 + DPT in L regions indicates favorable prognosis. These tumor‐associated DPT cells with similar phenotype are also verified in other tumors and HCC animal models. Single‐cell RNA‐seq further characterizes the molecular features of DPT cells and uncovers 11 clusters with different cytotoxicity, exhaustion, and activation scores. TCR‐based trajectory analysis reveals that tumor‐associated DPT clusters share separated ancestries with local CD4 + or CD8 + SPT cells rather than CD3 + PBMC cells. TCR clones with frequency above 10 are mainly found coexisting in DPT and CD8 + SPT cells. Specifically, PD‐1 high DPT cluster (TDPT_10) shares the same ancestry with exhausted CD8 + SPT cluster (TCD8T_2) and shows higher expression similarity and closer pathological location to PD‐1 + CD8 + than PD‐1 + CD4 + T cells. Together, this study systematically characterizes the unique distribution of PD‐1 + DPTs in HCC and puts forward new insights for the function and origin of tumor‐associated DPT cells. Abstract : A time‐of‐flight mass cytometry‐based single‐cell proteomic study is conducted to explore the immune heterogeneity in hepatocellular carcinoma. The tumor‐associated double‐positive T (DPT) cells are found enriched in L regions with expression of PD‐1/HLA‐DR/ICOS/CD45RO. Single‐cell RNA‐seq uncovers the 11 subclusters with different cytotoxicity, exhaustion, and activation. TCR‐seq reveals DPT cells share separated ancestries with local CD4 + or CD8 + SPT cells rather than CD3 + PBMC cells.